Processing, microstructure and mechanical properties of micro-SiC particles reinforced magnesium matrix composites fabricated by stir casting assisted by ultrasonic treatment processing - Wang, X.J.; Wang, N.Z.; Wang, L.Y.; Hu, X.S.; Wu, K.; Wang, Y.Q.; Huang, Y.D. (Materials in engineering, 2014)
•Novel stir casting assisted by ultrasonic treatment was developed.•Ultrasonic treatment significantly improved the stir casting.•Ultrasonic treatment improved the mechanical properties. The novel stir casting assisted by ultrasonic treatment processing was studied. Unlike traditional stir casting, short semi-solid stir time was needed for addition and pre-dispersion of the particles in the novel processing. For ultrasonic treatment, there existed an optimal time. Both too short and too long time for the treatment resulted in nonhomogeneous particle distribution. Furthermore, the liquid stirring after ultrasonic treatment was proved to be necessary to further improve particle distribution. The mechanical properties of the composites fabricated by different parameters indicated that ultrasonic treatment evidently improved the mechanical properties compared with traditional stir casting. 5–20% SiCp/AZ91 composites were fabricated by the novel processing. The particle distribution was uniform in these composites. The grains were refined by addition of SiC particles. Grain sizes of composites decreased with the increases of particle contents. The ultimate tensile strength, yield strength and elastic modulus were enhanced as the particle contents increased.